Resilient resistance? The third sector in the London Borough of Newham at a time of 'post-racial' politics. (February 2021) - Garratt, Lindsey; Byrne, Bridget; Harries, Bethan; Smith, Andrew
This article engages with the shift towards an emphasis on 'resilience' in local government discourses. Using the London Borough of Newham as a case study, it will argue that contradictory definitions of the term have, until recently, been used to justify the erosion of the third sector in the borough, specifically groups who support religious and linguistic minorities. Interviews and documentary analysis are used to consider how the concept of resilience had a racializing effect in this borough, and we argue that as a facet of policy resilience risks treating plurality as a threat rather than a strength. This is highlighted through an examination of how the third sector was characterised as retarding individuals' resilience and promoting 'ethno-centrism' in official resilience discourse. We offer three distinctive insights on the problem of resilience as a feature of policy, firstly, that resilience has a symbolic power that makes it difficult to securitize; secondly, resilience discourses risk instituting racism within policy; and thirdly, that resilience is built against collective forms of resistance and is therefore incapable of harnessing the resources and capacities of local populations. To conclude, we discuss the evolving political situation in the borough and the demise of the administration promoting resilience, through collective forms of resistance.